A study on prevalence of endometrial tuberculosis in unexplained infertility using cartridge-based nucleic acid amplification test - Basera, Ekta; Rastogi, Radha; Solanki, Lalita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Infertility is clinically defined as the inability to achieve pregnancy following one year of regular, unprotected intercourse. Its prevalence exhibits considerable variation across different regions, ranging between 5% and 20%. Extensive research has identified multiple etiological factors contributing to female infertility, including ovulatory dysfunction, infections of the genital tract, tubal obstruction, uterine abnormalities, endometriosis, endocrine disorders, and pelvic inflammatory diseases. Methods: The study was conducted in the Department of Obstetrics and Gynaecology at RNT Medical College and Allied Hospitals, Udaipur from January 2024 to December 2024, in collaboration with the Department of Microbiology. Result: Study finding shows that cartridge-based nucleic acid amplification test (CBNAAT) performed on endometrial samples. CBNAAT positivity was observed in 2 out of 70 women (2.86%), while 97.14% tested negative. The detected prevalence aligns closely with global estimates of genital tuberculosis in infertility, reinforcing the value of CBNAAT as a sensitive diagnostic tool in detecting paucibacillary forms of endometrial tuberculosis that might otherwise go undiagnosed through conventional methods. Conclusion: Study concludes a low prevalence, underscoring that genital tuberculosis may not be a frequent cause in cases labelled as unexplained infertility. While CBNAAT demonstrated high specificity (approaching 100%), its sensitivity remains low (around 22–25%), indicating that although a positive result strongly confirms disease, a negative result does not reliably exclude it.